2014
DOI: 10.1007/s13300-014-0065-z
|View full text |Cite
|
Sign up to set email alerts
|

Early Discontinuation and Restart of Insulin in the Treatment of Type 2 Diabetes Mellitus

Abstract: IntroductionAlthough the largest improvement in glycemic control occurs within the first 90 days of insulin therapy, little is known about early persistence on insulin therapy. This research aimed to identify predictors of early discontinuation and of subsequent restart of basal or mixture insulin among patients with type 2 diabetes mellitus (T2DM) and to assess the economic cost associated with such behaviors over a 1-year period.MethodsTruven’s Health Analytics Commercial Claims and Encounters database was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
80
4
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(86 citation statements)
references
References 24 publications
1
80
4
1
Order By: Relevance
“…This may in part be due to suboptimal persistence with insulin treatment in the real world care setting. For example, in a study of a large commercially insured insulin-na€ ıve population in the US, Ascher-Svanum et al found that only 18% of the people with T2DM who initiated insulin continued treatment in the year after initiation without any interruption or discontinuation 10 . With regards to basal insulin in particular, studies have found that approximately 55-80% of people with T2DM (identified from large commercial insurance databases) who were prescribed insulin glargine remained treatment persistent within the year after initiation [11][12][13][14] .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…This may in part be due to suboptimal persistence with insulin treatment in the real world care setting. For example, in a study of a large commercially insured insulin-na€ ıve population in the US, Ascher-Svanum et al found that only 18% of the people with T2DM who initiated insulin continued treatment in the year after initiation without any interruption or discontinuation 10 . With regards to basal insulin in particular, studies have found that approximately 55-80% of people with T2DM (identified from large commercial insurance databases) who were prescribed insulin glargine remained treatment persistent within the year after initiation [11][12][13][14] .…”
Section: Introductionmentioning
confidence: 99%
“…More recently, using pooled data from three different retrospective analyses of commercially insured populations, Wei et al reported that 65% of the people using insulin glargine or insulin detemir were treatment persistent within the year after initiation 17 Baser et al defined persistence as refilling the prescription within the 90th percentile of the time between the first and second refills among those with at least two refills, stratified by quantity supplied 11 . In all instances, however, people with an extended gap in insulin treatment were considered non-persistent even if they restarted therapy after initial discontinuation; a pattern commonly observed among people using insulin in the real world 10 . Therefore, it is important to gain a better understanding of the rates of basal insulin interruption and discontinuation separately.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A database study from the US indicated that early discontinuation of insulin (basal or premixed insulin) in type 2 diabetes was related to approximately 10% higher acute health care costs compared to patients who did continue their insulin therapy. 9 However, the costs related to early discontinuation from BOT (insulin glargine vs NPH ) have not yet been assessed. Therefore, the objective of this study is to describe the cost consequences of early discontinuation from initial basal insulin treatment (glargine, NPH insulin) in type 2 diabetes patients under real-world conditions in Germany.…”
mentioning
confidence: 99%